ANALYSIS OF RECEIVABLE TURNOVER AND WORKING CAPITAL ON COMPANY PROFITABILITY AT PT. BFI FINANCE INDONESIA, TBK - Ruth Veronika Butar-Butar; Aswin Akbar (Jurnal Ekonomi, 2023)
This study aims to analyze account receivable turnover and working capital on company profitability at PT. BFI Finance Indonesia Tbk. This study uses quantitative methods and secondary data used is the financial statements of PT. BFI Finance Indonesia Tbk for 2018-2022. The data analysis technique uses simple linear regression with the help of SPSS Statistics. The results showed that the coefficient of determination obtained by 0,396 or 39,6% showed that account receivable turnover and working capital was able to explain the variation in profitability in PT. BFI Finance Indonesia Tbk, while the remaining 60,4% was explained by other variables not studied in this study. The results showed that account receivable turnover partially had no significant effect on profitability and working capital had no significant effect on profitability, while simultaneously account receivable turnover and working capital had no effect on profitability.